PENINGKATAN REGULASI EMOSI ORANG TUA DALAM PENGASUHAN ANAK USIA 6–11 TAHUN MELALUI PSIKOEDUKASI DI KAWASAN WISATA KAYUTANGAN - khodijah shafira; Khansa Ufaira Zayyan; Kinanthi Alesia Putri; Madu Sekar Sari (FIP UNIRA MALANG, 2026)
Parenting school-aged children requires adequate emotional regulation skills, particularly amongmothers, as parental emotional responses play a crucial role in shaping parent–child interactionsand children’s emotional development. However, dual role demands, work-related stress, andparenting stress often trigger parental emotional dysregulation, leading to less adaptiveparenting practices. This community service activity aimed to enhance parental emotionalregulation and self-awareness in parenting children aged 6–11 years through psychoeducation inthe Kayutangan tourism area, Malang City. A pre-experimental method with a one-group pretest–posttest design was employed. Psychoeducation was provided to 16 mothers of children aged 6–11 years through interactive lectures, discussions, roleplay, and reflection sessions. Evaluation wasconducted using pre-tests and post-tests to assess changes in participants’ understanding ofemotional awareness, emotional regulation, and empathic communication. The results indicatedan improvement in mothers’ understanding and emotional readiness after participating in the psychoeducation program, as reflected by increased post-test scores among most participants.These findings suggest that psychoeducation is effective in strengthening parental emotionalregulation, thereby supporting more adaptive and emotionally supportive parenting practices.